Human Development Concept and Electrical System Simulation Using System Dynamics Model for Papua Province, Indonesia - Lefaan, Yosef; Dalimi, Rinaldy; Mollet, Julius Ary (International Journal of Energy Economics and Policy, 2019)
Development of human society (social), economic development, and environmental preservation are the three pillars of sustainable development. They must be implemented simultaneously and balanced. Two paradigms can be used to implement sustainable development, namely the economic development paradigm and the human development paradigm. This paper proposes a novel concept of human development in the Papua –Indonesia Province using a system thinking approach. This paper also proposes a novel modeling and simulation electrical system using a system dynamics method to fulfill human development demand. As an object of modeling and simulation, an electrical system in several regencies and municipality used. The simulation model results from the novel concept of human development in this study are projections of electricity demand and installed capacity of the 2016-2050 power plants in the BaU, moderate, and optimistic scenarios. Increased electricity demand and the installed capacity of the power plants are a function of the human development index (HDI) and development acceleration. The average increase in electricity demand is 3.8583; 5,0652; 8.1779 and 7.1122 percent per year for the BaU scenario, 0.5088; 0.3404; 1.1578 and 0.6726 percent per year for the moderate scenario, and 0.5100; 0.3422; 1.1694 and 0.6760 percent per year for optimistic scenario. The average increase in installed capacity of the power plant is 3.9880; 5,2110; 8.4366 and 7.3141 percent per year for the BaU scenario, 4.1159; 5,4391; 8.7747 and 7.6709 percent per year for the moderate scenario, and 4.470; 5,611; 9.1128 and 7.8392 percent per year for the optimistic scenario. Keywords: Human Development, System Thinking, System Dynamics, Papua-Indonesia. JEL Classifications: L94, O15, Q47, R58. DOI: https://doi.org/10.32479/ijeep.8301